Saturday : a novel - McEwan, Ian (New York : Anchor Books, 2006)
Saturday, February 15, 2003. Henry Perowne is a contented man - a successful neurosurgeon, the devoted husband of Rosalind, and proud father of two grown-up children. Unusually, he wakes before dawn, drawn to the window of his bedroom and filled with a growing unease. As he looks out at the night sky, he is troubled by the state of the world - the impending war against Iraq, a gathering pessimism since 9/11, and a fear that his city and his happy family life are under threat.
Keywords: Neurosurgeons -- Fiction; Psychological fiction